Legionella eukaryotic-like type IV substrates interfere with organelle trafficking. - Karim Suwwan de Felipe (Public Library of Science (PLoS), 2008)
Legionella pneumophila, the causative agent of Legionnaires' disease, evades phago-lysosome fusion in mammalian and protozoan hosts to create a suitable niche for intracellular replication. To modulate vesicle trafficking pathways, L. pneumophila translocates effector proteins into eukaryotic cells through a Type IVB macro-molecular transport system called the Icm-Dot system. In this study, we employed a fluorescence-based translocation assay to show that 33 previously identified Legionella eukaryotic-like genes (leg) encode substrates of the Icm-Dot secretion system. To assess which of these proteins may contribute to the disruption of vesicle trafficking, we expressed each gene in yeast and looked for phenotypes related to vacuolar protein sorting. We found that LegC3-GFP and LegC7/YlfA-GFP caused the mis-secretion of CPY-Invertase, a fusion protein normally restricted to the yeast vacuole. We also found that LegC7/YlfA-GFP and its paralog LegC2/YlfB-GFP formed large structures around the yeast vacuole while LegC3-GFP localized to the plasma membrane and a fragmented vacuole. In mammalian cells, LegC2/YlfB-GFP and LegC7/YlfA-GFP were found within large structures that co-localized with anti-KDEL antibodies but excluded the lysosomal marker LAMP-1, similar to what is observed in Legionella-containing vacuoles. LegC3-GFP, in contrast, was observed as smaller structures which had no obvious co-localization with KDEL or LAMP-1. Finally, LegC3-GFP caused the accumulation of many endosome-like structures containing undigested material when expressed in the protozoan host Dictyostelium discoideum. Our results demonstrate that multiple Leg proteins are Icm/Dot-dependent substrates and that LegC3, LegC7/YlfA, and LegC2/YlfB may contribute to the intracellular trafficking of L. pneumophila by interfering with highly conserved pathways that modulate vesicle maturation.